The path from childhood behavioural disorders to felony offending: Investigating the role of adolescent drinking, peer marginalisation and school failure. (24th September 2014) - Savolainen, Jukka; Mason, W. Alex; Bolen, Jonathan D.; Chmelka, Mary B.; Hurtig, Tuula; Ebeling, Hanna; Nordström, Tanja; Taanila, Anja
Abstract: Background: Although a pathway from childhood behavioural disorders to criminal offending is well established, the aetiological processes remain poorly understood. Also, it is not clear if attention deficit hyperactivity disorder (ADHD) is predictive of crime in the absence of comorbid disruptive behaviour disorder (DBD). Hypothesis: We examined two research questions: (1) Does ADHD have a unique effect on the risk of criminal offending, independently of DBD? (2) Is the effect of childhood behavioural disorders on criminal offending direct or mediated by adolescent processes related to school experience, substance misuse and peers? Method: Structural equation modelling, with latent variables, was applied to longitudinally collected data on 4644 men from the 1986 Northern Finland Birth Cohort Study. Results: Both ADHD and DBD separately predicted felony conviction risk. Most of these effects were mediated by adolescent alcohol use and low academic performance. The effect of DBD was stronger and included a direct pathway to criminal offending. Conclusion: Findings were more consistent with the life course mediation hypothesis of pathways into crime than the behavioural continuity path, in that the effects of each disorder category were mediated by heavy drinking and educational failure. Preventing these adolescent risk outcomes may be an effective approach to closing pathways to criminal behaviour amongst behaviourally disordered children. However, as there was some evidence of a direct pathway from DBD, effective treatments targeting this disorder are also expected to reduce criminal offending . Copyright © 2014 John Wiley & Sons, Ltd.